PENGELOLAAN DANA BANTUAN OPERASIONAL PERGURUAN TINGGI NEGERI (BOPTN) DALAM MENDUKUNG PROGRAM KERJA ORGANISASI MAHASISWA DI UNIVERSITAS NEGERI PADANG - M Lutfi Al Sahri; Zikri Alhadi (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2019)
ABSTRACT This study aims to determine the BOPTN fund management in supporting the work program of student organizations at Padang State University in managing BOPTN Padang State University fund. Good financial management planning does not yet have an ideal fund management system in accordance with POAC Planning Organizing Actuiting and Controling theory according to the results of research treated in a case study of BOPTN fund management in supporting the work programs of student organizations at Padang State University. The results showed that: the weakness of the BOPTN fund control system to student organizations, the many processes that must be passed by student organizations and there was no evaluation carried out by the university to student organizations after the distribution of funds. This caused the management and BOPTN not to be said by the State University student affairs department. Padang to support the work program of student organizations. that BOPTN fund management in supporting student work programs at Padang State University can be said to be going well with a few important notes that need to be more process of controlling funds and evaluating as well as understanding the management of BOPTN funds given from student to student organizations that need to be improved and become improvements forward.